The Heart and its Functions (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The cardiovascular system is a complex collection of blood vessels that carry substances between cells and blood and between blood and the environment. Its components are heart, blood vessels and blood. This article summarizes the necessary information about the physiology of the cardiovascular system. The heart is a person and satisfaction in the system central a ʼ zo , due to its constant contraction (systole), it drives blood through the circulatory system and ensures its return through veins and movement in arterial blood vessels.